Psychological well-being, mental distress, metabolic syndrome, and associated factors among people living in a refugee camp in Greece: a cross-sectional study - Knappe, Florian; Filippou, Konstantinia; Hatzigeorgiadis, Antonis; Morres, Ioannis D.; Tzormpatzakis, Emmanouil; Havas, Elsa; Seelig, Harald; Colledge, Flora; Ludyga, Sebastian; Meier, Marianne; de Quervain, Dominique; Theodorakis, Yannis; et al. (Frontiers in Public Health, 2023)
Background Forcibly displaced people face various challenges and are therefore at higher risk of being affected by mental and physiological distress. The present study aimed to determine levels of psychological well-being, PTSD symptom severity, metabolic syndrome, and associated factors among forcibly displaced people in Greece in response to WHO’s call for evidence-based public health policies and programs for forcibly displaced people. Methods We conducted a cross-sectional study among n = 150 (50% women) forcibly displaced people originating from Sub-Sahara Africa and Southwest Asia living in a Greek refugee camp. Self-report questionnaires were used to assess psychological well-being, symptoms of PTSD, depression, generalized anxiety disorder and insomnia, perceived stress, headache, and perceived fitness. Cardiovascular risk markers were assessed to determine metabolic syndrome, and cardiorespiratory fitness was measured with the Åstrand-Rhyming Test of Maximal Oxygen Uptake. Results The prevalence of mental distress and physiological disorders was overall elevated. Only 53.0% of participants rated their psychological well-being as high. Altogether, 35.3% scored above the clinical cut-off for PTSD, 33.3% for depression, 27.9% for generalized anxiety disorder, and 33.8% for insomnia. One in four (28.8%) participants met criteria for metabolic syndrome. While the prevalence of moderate or severe insomnia symptoms and metabolic syndrome differed little from the global population, the risk of being affected by mental distress was markedly increased. In multivariable analysis, higher perceived fitness was associated with higher psychological well-being (OR = 1.35, p = 0.003) and a decreased likelihood for metabolic syndrome (OR = 0.80, p = 0.031). Participants with elevated psychiatric symptoms were less likely to report high psychological well-being (OR = 0.22, p = 0.003) and had increased odds for higher PTSD severity (OR = 3.27, p = 0.034). Increased stress perception was associated with higher PTSD symptoms (OR = 1.13, p = 0.002). Conclusion There is an elevated risk for mental distress compared to the global population and an overall high mental and physiological burden among people living in a Greek refugee camp. The findings underpin the call for urgent action. Policies should aim to reduce post-migration stressors and address mental health and non-communicable diseases by various programs. Sport and exercise interventions may be a favorable add-on, given that perceived fitness is associated with both mental and physiological health benefits.